Radiographic and microbiologic evaluation of posttreatment apical and periapical repair of root canals of dogs' teeth with experimentally induced chronic lesion - Leonardo, Mário Roberto [UNESP]; Almeida, Walter Autonio [UNESP]; Ito, Izabel Yoko; da Silva, Léa Assed Bezerra (Elsevier, 1994)
The objective of the present study was to evaluate radiographically and bacteriologically apical and periapical repair in dogs' teeth with induced chronic periapical lesions with the use of two different operative techniques (techniques 1 and 2). The study was conducted on 40 root canals of upper and lower premolars from two dogs aged approximately 12 months. Periapical lesions were induced by leaving the root canals exposed to the oral environment for 5 days and then sealing them with zinc oxide-eugenol for 45 days. After this period, radiographic examination revealed the occurrence of a radiolucent lesion and endodontic treatment was started. The two techniques did not differ in terms of chemomechanical preparation, final filling, or type of cement, but differed in terms of irrigating solution and the presence of an antibacterial dressing. Thus 4% to 6% hypochlorite and hydrogen peroxide (10 volumes) were used in technique 1 during chemomechanical preparation and an antibacterial dressing based on calcium hydroxide was applied between sessions, whereas Dakin's fluid (0.5% sodium hypochlorite solution) and a final filling with no antibacterial dressing were used in technique 2. After chemomechanical preparation, the root canals were filled with gutta-percha cones and Sealapex (Sealapex-Sybron, Kerr, Sao Paulo, Brazil), and the animals were killed 270 days after the final filling. Blocks were cut into 6-μm sections and stained by the Brown and Brenn method. Radiographic, histomicrobiologic and statistical analysis permitted us to conclude the following: radiographically there was a marked reduction or even the disappearance of the radiolucent area present before treatment with greater success in the group treated with technique 1 (group I) than in the group treated with technique 2 (group II); the extent of bacterial invasion of dentinal tubules was greater and more intense in group II than in group I; and the amount of microorganisms detected in the ramifications of the apical delta and in the lumen of the root canal was intense in group II and mild or absent in group I. © 1994.
Keywords: Anti Infective Agents; antiinfective agent; biomedical and dental materials; calcium hydroxide; camphor; camphorated parachlorophenol; chlorophenol; endotoxin; hydrogen peroxide; hypochlorite sodium; animal; bacterial infection; cementum; chi square distribution; chronic disease; comparative study; dentin; dog; drug combination; endodontics; Gram positive bacterium; isolation and purification; methodology; microbiology; radiography; tooth periapical disease; tooth pulp; Animal; Anti-Infective Agents; Bacterial Infections; Calcium Hydroxide; Camphor; Chi-Square Distribution; Chlorophenols; Chronic Disease; Comparative Study; Dental Cementum; Dental Pulp Cavity; Dentin; Dogs; Drug Combinations; Endotoxins; Gram-Positive Bacteria; Hydrogen Peroxide; Periapical Periodontitis; Root Canal Irrigants; Root Canal Therapy; Sodium Hypochlorite